2023
DOI: 10.1186/s12957-023-03062-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of sentinel lymph node biopsy in elderly patients with breast cancer – 10-year experience from a Swiss university hospital

Abstract: Background The Choosing Wisely initiative recommended the omission of routine sentinel lymph node biopsy (SLNB) in patients ≥ 70 years of age, with clinically node-negative, early stage, hormone receptor (HR) positive and human epidermal growth factor receptor 2 (Her2) negative breast cancer in August 2016. Here, we assess the adherence to this recommendation in a Swiss university hospital. Methods We conducted a retrospective single center cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Whilst results from the remaining trials on the omission of SLNB are pending, an important quest will be to integrate these results into real-world practice, as it was repeatedly shown that the Choosing Wisely recommendations were not followed in clinical practice [38][39][40]. Possible reasons for this are the categorization of SLNB as a low-risk procedure, the lost pathological staging information, and the partial lack of compatibility with inclusion criteria in some of the major trials on radiotherapy-omission and hypofractionation [41][42][43][44][45].…”
Section: Patients With Clinically and Imaging Node-negative Breast Ca...mentioning
confidence: 99%
“…Whilst results from the remaining trials on the omission of SLNB are pending, an important quest will be to integrate these results into real-world practice, as it was repeatedly shown that the Choosing Wisely recommendations were not followed in clinical practice [38][39][40]. Possible reasons for this are the categorization of SLNB as a low-risk procedure, the lost pathological staging information, and the partial lack of compatibility with inclusion criteria in some of the major trials on radiotherapy-omission and hypofractionation [41][42][43][44][45].…”
Section: Patients With Clinically and Imaging Node-negative Breast Ca...mentioning
confidence: 99%